Representation Of Women in Indonesian Horror Movie Posters: From Victims to Iconic Mystical Figures - Andriani, Nanda Putri; Murtono, Taufik (West Science Social and Humanities Studies, 2025)
The study focuses on the representation of women in Indonesian horror movie posters, particularly those depicting women as victims of violence or supernatural beings. It aims to analyze how these posters reinforce gender stereotypes and patriarchal ideologies that shape societal perceptions of women. The research employs Van Dijk's discourse analysis method, encompassing three levels: text structure, social cognition, and social context. Four Indonesian horror movie posters from 2023 were visually and narratively analyzed. The findings reveal that most posters perpetuate gender bias by depicting women as passive or vulnerable figures, thus reinforcing dominant patriarchal narratives. Notably, the poster for Suzzanna: Malam Jumat Kliwon presents a contrast, portraying the female figure as powerful and threatening. Although this depiction still operates within the supernatural framework, it suggests a shift toward a more active and empowered female presence. Overall, the study highlights the complex dynamics of gender representation in horror media and its implications for broader cultural discourses.